2011
DOI: 10.1055/s-0029-1246012
|View full text |Cite
|
Sign up to set email alerts
|

Outcome and Quality of Life Favour a Conservative Treatment of Patients with Primary Gastric Lymphoma

Abstract: Long-term outcome of patients with gastric lymphoma is excellent irrespective of the lymphoma type and the treatment approach. Considering quality of life a conservative therapeutic strategy should be favoured.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 6 publications
0
14
0
5
Order By: Relevance
“…A 2011 study comparing the two types of treatments using the Gastro Intestinal Quality of Life Index (GLQI) found that, after treatment for gastric lymphoma, "Posttherapeutic quality of life was generally high with a significant advantage for patients treated conservatively compared to those who underwent surgery" [17]. Showing a more favorable outcome of quality of life after chemotherapy compared to after a gastrectomy for gastric lymphoma patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A 2011 study comparing the two types of treatments using the Gastro Intestinal Quality of Life Index (GLQI) found that, after treatment for gastric lymphoma, "Posttherapeutic quality of life was generally high with a significant advantage for patients treated conservatively compared to those who underwent surgery" [17]. Showing a more favorable outcome of quality of life after chemotherapy compared to after a gastrectomy for gastric lymphoma patients.…”
Section: Discussionmentioning
confidence: 99%
“…The results also support the findings of a 2011 study that concluded, "long-term outcome of patients with gastric lymphoma is excellent irrespective of the lymphoma type and the treatment approach. Considering quality of life a conservative therapeutic strategy should be favored" [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are two strong arguments for such a recommendation: equal treatment outcomes after surgical or conservative strategies and a better quality of life with a stomach-preserving therapy. The latter has been clearly demonstrated by a prospective randomized trial with a 10-year follow-up [15]. …”
Section: Therapeutic Options In Gastric Malt Lymphomamentioning
confidence: 96%
“…Bei fehlender Überlegenheit der Chirurgie gegenüber den konservativen Therapieverfahren wiegt der Aspekt der Lebensqualität nach organerhaltender Therapie schwerer stellt ein eindeutiges Argument gegen die chirurgische Resektion dar [20]. Eine Operation ist heute nur noch bei Komplikationen wie einer endoskopisch nicht beherrschbaren Blutung oder Perforation indiziert.…”
Section: Operationunclassified